LINGUISTIC AND NEUROPSYCHOLOGICAL ANALYSIS OF LANGUAGE PRODUCTION IN 4-6-YEAR-OLD GEORGIAN-SPEAKING CHILDREN WITH TYPICAL LANGUAGE DEVELOPMENT AND SPECIFIC LANGUAGE DISORDER - Doghadze , Irine; Gagoshidze , Tamar (Georgian Psychological Journal, 2022)
The present ﬆudy aimed at conducting the neuropsychological and linguiﬆic analysis of expressive lan- guage disorder in the population of Georgian-speaking children. 4-6-year-old children with expressive language disorder and typical language development participated in the ﬆudy (40 participants in total). The child’s speech was assessed through formal teﬆing and free play in informal situations. The comparison of the two groups showed that the children with typical language development signiﬁ- cantly diﬀer from the group with language disorder by articulation (t (38) = - 4,65, p<0,001), phono- logical (t (38) = - 2,48, p<0,05), and syntactic errors (t (38) = - 3,67), length of utterance (t (38) = 3,62, p=0,001), and the total number of errors (t (38) =- 5,36, p<0,001). The above data lead to the following conclusion: Georgian-speaking children with expressive language disorder moﬆly make phonological, syntactic and articulation errors. They also ﬁnd diﬃcult to conﬆruct complex sentences. The comparison of the two groups did not reveal qualitative diﬀerences. Both groups made the same type of miﬆakes. The only diﬀerence was the total number of errors. Regression analysis showed that the length of utterance and the total production can only predict the type of errors in average population.The interpretation of the research results leads to four general conclusions: 1. Expressive language disorder is not atypical language development disorder and only implies prolonged language acqui- sition; 2. The deﬁciency proﬁle manifeﬆed in the case of expressive language disorder depends on a concrete language and the requirements imposed on the child by this language; 3. Phonetic, articulation, syntactic errors and short sentences are moﬆly typical of Georgian-speaking children with expressive language disorder; 4. According to Levelt’s cognitive model, the ﬆage of grammatical and phonological encoding and the ﬆage of articulation of phonetic plan are the deﬁcient links in the population of Geor- gian-speaking children.